Application and evaluation of Tip Enhanced Raman Spectroscopy in pharmaceutical analysis - Papakostas, G (2022)
Pharmaceutical analysis plays a crucial role in drug manufacturing, allowing the identification and exploration of the physio-chemical properties and interactions between active pharmaceutical ingredients (API) and excipients within a formulation. However, conventional microscopy instruments can be constrained in resolving chemical information below the micron-length scales. A newly arising nano-analytical technique is the Tip-Enhanced Raman Spectroscopy (TERS), which can obtain valuable spatio-chemical information from the sample of interest, at the length scales of tens of nanometres or less. TERS application has been reported on numerous carbon-based and biological samples, however to-date there are no records of TERS application on pharmaceutical formulations.